Design and characterization of a circularly polarized microstrip-line-fed slot array antenna for S-band applications - Das, Debprosad; Hossain, Md. Farhad; Hossain, Md. Azad (International Journal of Electrical and Computer Engineering (IJECE), 2023)
A 2×2 slot array antenna fed by microstrip line for circular polarization operated in the S band frequency range is designed in this paper. Single cross slot with single port feed as well as dual port feed is taken into consideration for realizing circular polarization and combining these two processes, the slot array is designed with single feed for circular polarization. The antennas are designed on a Teflon glass fiber substrate of thickness 0.8 mm. The slot array dimension is 120×142×1.636 mm3. Smith chart of single cross slot antenna with single feed as well as dual feed has a dip at 2.69 and 2.53 GHz respectively indicate the capability of realizing circular polarization in the S band frequency range. The return loss of the slot array antenna is -58 dB shows good input impedance matching of the antenna. A dip in the smith chart of the slot array shows circular polarization near 2.4 GHz ensuring wireless applications as well. Axial ratio is found to be less than 1 dB in the resonance frequency. The impedance bandwidth percentage of the slot array antenna is 12.24%. The simulation is done by using keysight advanced design system (ADS) software.